Genotypic Variability and Character Associations of Kabuli Chickpea (Cicer artietinum L.) Genotypes for Yield and Yield Related Traits at Arsi-Robe, Southeastern Ethiopia - Kebede, Gizachew Yilma; Tesso, Bulti; Alemu, Tesfahun (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted at Arsi-robe, Southeast Ethiopia during August–December, 2020 to understand the extent of genetic variability and association for yield and yield related traits among Kabuli chickpea genotypes. Forty-nine Kabuli chickpea genotypes were evaluated for 11 traits at Arsi-robe using 7×7 simple lattice designs. The analysis of variance showed significant differences among genotypes. The phenotypic variances of the traits were higher than the genotypic variances, implying the influence of environment on the expression of the traits. Genotypic coefficient of variation (GCV) ranged from 1.28 for days to maturity to 41.74% for grain yield and phenotypic coefficient of variation (PCV) ranged from 1.47 to 44.06% for days to maturity and grain yield, respectively. High heritability was recorded from grain yield. High broad-sense heritability coupled with high genetic advance was observed for grain yield, number of secondary branches and hundred seed weight. Grain yield showed highly significant and positive genotypic correlations with grain filling period, number of seed plant-1 and plant height. Genotypic path coefficient analysis showed that days to maturity, number of pods plant-1, number of seed plant-1, plant height and hundred seed weight had positive direct effects on grain yield. Number of pods plant-1 exhibited a maximum positive direct effect on grain yield. The observed variations indicate the possibility for further improvement of grain yield and associated traits by utilizing selected parental genotypes and targeted crossing schemes in breeding programs.